Patient cardiovascular risk self-management: results from a randomized trial of motivational interviewing delivered by practice nurses - Huntink, Elke; Koetsenruijter, Jan; Wensing, Michel (Family practice, 2019)
Abstract Background. To enhance cardiovascular risk management and patients’ self-management, a tailored programme to improve cardiovascular risk management was